A logic programming approach to knowledge-state planning, II: The [formula omitted] system - Eiter, Thomas; Faber, Wolfgang; Leone, Nicola; Pfeifer, Gerald; Polleres, Axel (Artificial intelligence, 2003)
In Part I of this series of papers, we have proposed a new logic-based planning language, called K . This language facilitates the description of transitions between states of knowledge and it is well suited for planning under incomplete knowledge. Nonetheless, K also supports the representation of transitions between states of the world (i.e., states of complete knowledge) as a special case, proving to be very flexible. In the present Part II, we describe the DLV K planning system, which implements K on top of the disjunctive logic programming system DLV. This novel planning system allows for solving hard planning problems, including secure planning under incomplete initial states (often called conformant planning in the literature), which cannot be solved at all by other logic-based planning systems such as traditional satisfiability planners. We present a detailed comparison of the DLV K system to several state-of-the-art conformant planning systems, both at the level of system features and on benchmark problems. Our results indicate that, thanks to the power of knowledge-state problem encoding, the DLV K system is competitive even with special purpose conformant planning systems, and it often supplies a more natural and simple representation of the planning problems.